1992
DOI: 10.1007/bf01158810
|View full text |Cite
|
Sign up to set email alerts
|

Monotone control of queueing networks

Abstract: This paper uses submodularity to obtain monotonicity results for a class of Markovian queueing network service rate control problems. Nonlinear costs of queueing and service are allowed. In contrast to Weber and Stidham [14], our monotonicity theorem considers arbitrary directions in the state space (not just control directions), arrival routing problems, and certain uncontrolled service rates. We also show that, without service costs, transitionmonotone controls can be described by simple control regions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 11 publications
0
37
0
1
Order By: Relevance
“…The relations (15) show that the structural and monotone properties of the optimal control policy f can be derived by analysing the monotonicity properties of the value function v. Such properties for other types of controlled queues in a tandem were studied also in [12,15,31]. It was shown that the value function has some monotonicity properties like non-decreasing and superconvexity.…”
Section: Corollary 1 the Optimal Policymentioning
confidence: 99%
“…The relations (15) show that the structural and monotone properties of the optimal control policy f can be derived by analysing the monotonicity properties of the value function v. Such properties for other types of controlled queues in a tandem were studied also in [12,15,31]. It was shown that the value function has some monotonicity properties like non-decreasing and superconvexity.…”
Section: Corollary 1 the Optimal Policymentioning
confidence: 99%
“…The policy is monotone if it satisfies 1. Monotone switching: See Veatch and Wein (1992) for a discussion of monotonicity. Ha (1992) proves that the optimal policy is monotone for the case of two products with 碌 1 = 碌 2 and backordering.…”
Section: Dynamic Scheduling Problemmentioning
confidence: 99%
“…We extend this result to cover the case when the server can serve at either station and also to include machine breakdowns. Our approach establishes properties of the value function directly, rather than showing that properties are preserved by value iteration as in Hajek [4] and Veatch and Wein [6].…”
Section: Introductionmentioning
confidence: 99%